Pelatihan Manajemen Waktu Pada Stres Akademik Karyawan Penuh Waktu - Cinthia Annisa Vinahapsari; Rosita Rosita (Jurnal Bisnis Darmajaya, 2020)
The purpose of this study is to analyse the effectiveness of time management training on academic stress employees who are registered as students at private universities in Bandarlampung. This study was conducted in Bandarlampung with a population of 60 fulltime employees. The sample are employee who actively works and holds managerial positions in the company and registered as a student at the university. This study is quantitative method using smartPLS 3.0. software. The results revealed 2 major finding. (1) time management training had a negative and significant effect on employee’s academic stress; (2) By understanding the concept of time management, and setting goals and priorities abilities be able to reduce the employee's academic stress. Keywords: Time Mangement Traning, Academic Stress, Fulltime Employee